On 3-dimensional f-Kenmotsu manifolds and Ricci solitons - Yildiz, A.; De, U.C.; Turan, M. (Український математичний журнал, 2013)
The aim of the present paper is to study 3-dimensional f-Kenmotsu manifolds and Ricci solitons. First, we give an example of a 3-dimensional f-Kenmotsu manifold. Then we consider a Riccisemisymmetric 3-dimensional f-Kenmotsu manifold and prove that a 3-dimensional f-Kenmotsu manifold is Ricci semisymmetric if and only if it is an Einstein manifold. Moreover, we investigate an η-parallel Ricci tensor in a 3-dimensional f-Kenmotsu manifold. Finally, we study Ricci solitons in a 3-dimensional f-Kenmotsu manifold. Метою даної статті є вивчення 3-вимірних f-многовидів Кенмоцу та солітонів Річчі. Спочатку наведено приклад 3-вимірного f-многовиду Кенмоцу. Потім розглянуто напівсиметричний за Річчі 3-вимірний f-многовид Кенмоцу i доведено, що 3-вимірний f-многовид Кенмоцу є напівсиметричним за Річчі тоді i тільки тоді, коли він є многовидом Ейнштейна. Також досліджено n-паралельний тензор Річчі у 3-вимірному f-многовиді Кенмоцу. Насамкінець, досліджено солітони Річчі у 3-вимірному f-многовиді Кенмоцу.